Determination of the largest Lyapunov exponent of chaos in the dynamics of hazardous parameters of a gas environment for the rapid ignition detection - Tolok, Igor; Pospelov, Boris; Rybka, Evgenіy; Savchenko, Serhii; Kozar, Yurii; Krainiukov, Olekcii; Sporyshev, Konstantin; Maladyka, Larysa; Surianinov, Vyacheslav; Harifullin, Maksym (Technology audit and production reserves, 2025)
The object of research is the largest Lyapunov exponent of the dynamics of hazardous gas environment parameters in premises at intervals of reliable absence and presence of ignition of materials in premises. The problem is to determine and develop a strategy for using the largest Lyapunov exponent on a one-dimensional sample of real contaminated measurements of hazardous gas environment parameters in premises for the prompt detection of material ignitions. An experimental verification of the determination of the largest Lyapunov exponent of the dynamics of the main hazardous gas environment parameters during ignition of materials in a laboratory chamber at intervals of reliable absence and occurrence of ignition was performed. It was established that during ignition of materials, the values of the largest Lyapunov exponent indicate a decrease in stability and a transition to chaos in the dynamics of temperature and carbon monoxide concentration for all the test materials under study. This indicates a loss of the degree of “order” in the dynamics of temperature and carbon monoxide concentration. At the same time, the value of the largest Lyapunov exponent of the dynamics of the specific optical density of smoke does not change significantly and remains stable with some decrease in stability during ignition of the material. It was found that the use of such a parameter for detecting the ignition of materials has significant advantages in the case of using the dynamics of temperature and carbon monoxide concentration of the gas environment of the premises. The results obtained are useful from a theoretical point of view for determining the largest Lyapunov exponent for a one-dimensional sample of real contaminated measurements for an arbitrary dangerous parameter of the gas environment at an arbitrary observation interval. The practical significance lies in the possibility of further improving existing fire protection systems of objects in order to prevent fires.